Conversion Disorder Mimicking Dejerine-Roussy Syndrome (Thalamic Stroke) After Spinal Cord Stimulation. Issue 2 (1st March 2004) - Ferrante, F. Michael; Rana, Maunak V.; Ferrante, Margaret A.
Abstract : Objective: Dejerine-Roussy syndrome is a complex of various signs and symptoms in patients suffering from central thalamic pain, usually secondary to a vascular etiology. We describe a patient presenting with the potentially devastating signs and symptoms of thalamic stroke, at least temporally related to spinal cord stimulator implantation. The etiology of the patient's affliction was subsequently revealed to be a conversion disorder. Case Report: A 37-year-old woman presented for spinal cord stimulation as treatment of her brachial plexopathy after failure of conservative therapy. Before implantation, she underwent a clinical interview with a psychologist and psychometric testing. No psychological pathology was detected. Trial and permanent implantation of the cervical stimulator lead and pulse generator were uneventful. Eleven days after receiving the permanent implant, the patient experienced right-sided hemicorporal numbness and burning dysesthesia. The patient was admitted, and a diagnosis of Dejerine-Roussy syndrome (thalamic stroke) was made. She was discharged, and her symptomatology waxed and waned over a period of weeks. The patient was subsequently admitted for psychiatric evaluation because of anxiety attacks. During her protracted admission, her psychiatrists strongly suspected a conversion disorder. The stimulator was removed, and the patient received supportive care only. Within 6 months, sensory symptoms and all motor deficits had completely resolved. Conclusions: Despite careful preoperative evaluation, latent psychosocial issues may limit the effectiveness of spinal cord stimulation. We present a case of conversion disorder masquerading as Dejerine-Roussy syndrome after spinal cord stimulation. The implications of the failure of preoperative psychological evaluation and screening to avert implantation are discussed.